Axial development of air–water annular flow with swirl in a vertical pipe. (March 2020) - Liu, Wen; Lv, Xiaofei; Bai, Bofeng
Highlights: Experiment shows that swirling annular flow decays quickly and finally transforms to non-swirl flow downstream of the swirler. Axial development of void fraction and pressure drop in the decayed swirl flow has been investigated. A simplified theoretical model was developed to qualitatively predict the decay in a swirling annular flow. Frictional pressure drop in the annular flow with swirl can be predicted by the model established here. Abstract: Annular flow with swirl induced by a swirler has been widely used in industry. Swirl decay which closely related to working performance and length of the flow is significantly important for its application in industry. Axial development of annular flow with and without swirl has been investigated in this work by means of experimentation and modelling. A vertical pipe system with 11 m long and 62 mm inner diameter was carried out to investigate axial development of flow pattern, void fraction and pressure drop in the annular flow with and without swirl. The experimental results show that a swirling annular flow with swirling streak and less disturbed waves is observed downstream of the swirler. Void fraction decreases, total pressure drop increases and the PDF (probability density function) of pressure drop becomes more concentrated in the annular flow with swirl, compared with these in the annular flow without swirl. However, swirling annular flow is gradually transformed to annular flow without swirl along the streamwise direction. To qualitatively predict the decay in an annular flow with swirl, a simplified theoretical model was developed here. The results calculated with the theoretical model were in agreements with experimental results. The obtained results can be used in predicting working performance and length of devices, such as separators and heat exchangers.